Chemerin is an antimicrobial agent in human epidermis. - Magdalena Banas; Katarzyna Zabieglo; Gopinath Kasetty; Monika Kapinska-Mrowiecka; Julia Borowczyk; Justyna Drukala; Krzysztof Murzyn; Brian A Zabel; Eugene C Butcher; Jens M Schroeder; Artur Schmidtchen; Joanna Cichy (PLoS ONE, 2013)
Chemerin, a chemoattractant ligand for chemokine-like receptor 1 (CMKLR1) is predicted to share similar tertiary structure with antibacterial cathelicidins. Recombinant chemerin has antimicrobial activity. Here we show that endogenous chemerin is abundant in human epidermis, and that inhibition of bacteria growth by exudates from organ cultures of primary human skin keratinocytes is largely chemerin-dependent. Using a panel of overlapping chemerin-derived synthetic peptides, we demonstrate that the antibacterial activity of chemerin is primarily mediated by Val(66)-Pro(85), which causes direct bacterial lysis. Therefore, chemerin is an antimicrobial agent in human skin.